Improving the Performance of Higher Education in Vietnam : Strategic Priorities and Policy Options - World Bank (World Bank, Washington, DC, 2020)
The progress of East Asian economies in recent years illustrates a strong symbiotic relationship among higher education, innovation, and growth through the production of research and skills. In the case of Vietnam, higher education has a significant positive effect on household poverty and long-term earnings at the individual level, where annualized private returns to higher education are above fifteen percent, one of the highest levels in the world. As Vietnam aspires to become an upper middle-income country by 2035, its productivity needs to increase continuously, which requires greater production and effective use of highskilled manpower and science, technology and innovation (STI). There is a disconnect between Vietnam’s remarkable achievement on equitable economic growth and human development, on the one hand, and the performance of the higher education system, on the other hand. Vietnam has experimented with a number of higher education reforms in the last two decades, with some success in expanding access but missing opportunities in achieving good results on quality and relevance, and in furthering equity. The main objective of this Bank’s report is to provide a diagnosis of the current performance of the Vietnamese universities and propose a range of options for transforming and developing the higher education system.